2019
DOI: 10.1161/circresaha.118.313221
|View full text |Cite
|
Sign up to set email alerts
|

Device-Based Neuromodulation for Resistant Hypertension Therapy

Abstract: Despite availability of effective drugs for hypertension therapy, significant numbers of hypertensive patients fail to achieve recommended blood pressure (BP) levels while on ≥3 antihypertensive drugs of different classes. These individuals have a high prevalence of adverse cardiovascular events and are defined as having resistant hypertension (RHT) although nonadherence to prescribed antihypertensive medications is common in patients with apparent RHT. Furthermore, apparent and true RHT often display increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 177 publications
1
51
1
Order By: Relevance
“…Based on the results of animal studies, renal denervation and baroreflex activation therapy, which suppresses the increase in central sympathetic activity, has been attempted as a treatment for treatment-resistant hypertension in humans, and both have been reported to lower blood pressure and, in addition, to exert therapeutic effects on heart failure. 12,13 SGLT2 inhibitors inhibit overactivation of the sympathetic nervous system Sympathetic nervous system activation is associated with hospitalization and death in heart failure. 14 It has been shown that in diabetic patients, as in hypertensive patients, there is an overactivation of the systemic sympathetic nervous system.…”
Section: Renal Stress Causes the Activation Of Sympathetic Nervous Symentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of animal studies, renal denervation and baroreflex activation therapy, which suppresses the increase in central sympathetic activity, has been attempted as a treatment for treatment-resistant hypertension in humans, and both have been reported to lower blood pressure and, in addition, to exert therapeutic effects on heart failure. 12,13 SGLT2 inhibitors inhibit overactivation of the sympathetic nervous system Sympathetic nervous system activation is associated with hospitalization and death in heart failure. 14 It has been shown that in diabetic patients, as in hypertensive patients, there is an overactivation of the systemic sympathetic nervous system.…”
Section: Renal Stress Causes the Activation Of Sympathetic Nervous Symentioning
confidence: 99%
“…Based on the results of animal studies, renal denervation and baroreflex activation therapy, which suppresses the increase in central sympathetic activity, has been attempted as a treatment for treatment-resistant hypertension in humans, and both have been reported to lower blood pressure and, in addition, to exert therapeutic effects on heart failure. 12 , 13 …”
Section: Renal Stress Causes the Activation Of Sympathetic Nervous Symentioning
confidence: 99%
“…The BAROSTIM NEO® Pivotal Trial (NCT01679132) was designed as a single-group open-label trial including 10 participants. However, this trial was suspended, since the company focused on other studies [35]. Currently, two large randomized controlled trials for baroreceptor activation therapy are carried out, investigating the unilateral BAROSTIM NEO® System.…”
Section: Carotid Sinus Stimulationmentioning
confidence: 99%
“…40 Although BAT received little or no attention for decades thereafter, primarily due to successful drug development, an increasing need for alternative treatment approaches for resistant hypertension and heart failure has prompted renewed research in this area. 35,[41][42][43]…”
Section: The Concept Of Baroreflex Activation Therapymentioning
confidence: 99%